The Perinatal Quality Collaborative of North Carolina’s 39 Weeks Project: A Quality Improvement Program to Decrease Elective Deliveries Before 39 Weeks of Gestation - Berrien, Kate (N C Med J, 2014)
BACKGROUND: Despite long-standing guidelines from the American College of Obstetricians and Gynecologists that call for avoiding elective births prior to 39 weeks of gestation, elective deliveries make up almost one-third of US births occurring in weeks 36–38. Poor outcomes are more likely for infants born electively before 39 weeks than for those born at 39 weeks. The Perinatal Quality Collaborative of North Carolina (PQCNC) undertook the 39 Weeks Project in 2009–2010 with the aim of reducing the number of early-term elective deliveries in North Carolina hospitals. METHODS: Participating hospitals (N = 33) provided retrospective data on all early-term deliveries and created new policies, or amended or enforced existing policies, to accomplish the project’s goals. Project activities included in-person learning sessions, regional meetings, webinars, electronic newsletters, a secure extranet Web site where participating hospitals could share relevant materials, and individual leadership consultations with hospital teams. Hospitals submitted monthly data to PQCNC, which provided ongoing training and data analysis. RESULTS: Elective deliveries before 39 weeks of gestation decreased 45% over the project period, from 2% to 1.1% of all deliveries. The proportion of elective deliveries among all scheduled early-term deliveries also decreased, from 23.63% to 16.19%. There was an increase in the proportion of patients with documented evidence of medical indications for early delivery, from 62.4% to 88.2%. LIMITATIONS: No data were collected to determine whether outcomes changed for patients whose deliveries were deferred. The project also depended on each hospital to code its own data. CONCLUSIONS: The PQCNC’s 39 Weeks Project successfully decreased the rate of early-term elective deliveries in participating hospitals.